PENGEMBANGAN MODEL MATEMATIKA JARINGAN SUPPLY CHAIN DENGAN MEMPERTIMBANGKAN EMISI PADA INDUSTRI DAUR ULANG KERTAS - Asgar Ali; Nur Aini Masruroh (Jurnal Teknosains, 2016)
Recycling is part of the green supply chain management which is developed base on the concept of environmentally friendly industry to respond the various issues regarding the environmental problems of the world. Distribution of recycled products starts from consumers and ends to manufacturing. The objective is to limit the waste in order to save energy and prevent the dumping of hazardous materials into the environment. However there are complexities in the supply chain because of some uncertainties such as the return of recycled product and the environmental impact resulting from the operation of supply chain. In this research, linear programming optimization method is proposed to overcome that problem with maximizing profit is set as the objective function. Emissions resulting from the recycling process are considered in the model. These results indicate that the mathematical model provides profit of Rp. 37.909.659, with 1.137.760 grams of CO2 emissions from the production process, 38.473,4 grams of CO and 5.884,9 grams HC + NOX of transport. While the proposed strategy is use the right vehicles and select the most efficient route according to the paper collected from consumers and sold to manufacturing. For the production process, it is required to add 3 pressing machines and 1 chopped machine, so the capacity of the working hours of 384 hours per month can be increased to 960 hours per month.